2021
DOI: 10.3390/nano11113042
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Easy Magnetization Direction and Magnetostatic Interactions in High Aspect Ratio Nanowires

Abstract: Cobalt nanowires have been synthesized by electrochemical deposition using track-etched anodized aluminum oxide (AAO) templates. Nanowires with varying spacing-to-diameter ratios were prepared, and their magnetic properties were investigated. It is found that the nanowires’ easy magnetization direction switches from parallel to perpendicular to the nanowire growth direction when the nanowire’s spacing-to-diameter ratio is reduced below 0.7, or when the nanowires’ packing density is increased above 5%. Upon fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The shape anisotropy favors easy magnetization direction along the nanorods' length whereas dipolar interactions favor it perpendicular to nanorods' length. Our previous work on Co nanowires [42] indicated that center to center spacing in nanowires arrays plays decisive role to align easy magnetization direction along or perpendicular to their growth direction. The center to center spacing directly impacts packing density (magnetic content) of the nanorods arrays, that is fixed with the AAO template pore density [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape anisotropy favors easy magnetization direction along the nanorods' length whereas dipolar interactions favor it perpendicular to nanorods' length. Our previous work on Co nanowires [42] indicated that center to center spacing in nanowires arrays plays decisive role to align easy magnetization direction along or perpendicular to their growth direction. The center to center spacing directly impacts packing density (magnetic content) of the nanorods arrays, that is fixed with the AAO template pore density [42].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work on Co nanowires [42] indicated that center to center spacing in nanowires arrays plays decisive role to align easy magnetization direction along or perpendicular to their growth direction. The center to center spacing directly impacts packing density (magnetic content) of the nanorods arrays, that is fixed with the AAO template pore density [42]. The estimated packing density of our templates is 12% that is much higher than the required density for the shape anisotropy to overcome dipolar interactions and hence easy magnetization direction favors perpendicular to nanorods' length [1].…”
Section: Resultsmentioning
confidence: 99%
“…To obtain nanostructure coated carbon cloths, the metal nanostructures were deposited within the channels of the carbon cloth following the optimized fabrication conditions and protocols 22 , 23 which involved electrochemical deposition in the two-electrode cell with a bath volume of 20 ml. All depositions were performed at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In this Special Issue, there are research articles that focus on the thin film growth of ferromagnetic/semiconducting heterostructures and their relation to structural, magnetic, and transport properties [ 1 , 2 , 3 , 4 ], as well as Heusler alloys with ferromagnetic and Weyl semimetals behavior [ 1 , 5 ].…”
mentioning
confidence: 99%